Percutaneous Transhepatic Cholangiography. Issue 4 (December 1960) - Atkinson, Michael; Happey, Margaret G.; Smiddy, Francis G.
Abstract : This is an evaluation of percutaneous transhepatic cholangiography, a technique of over eight years' standing, previously considered by many authorities as both unrewarding and dangerous. The value and risks of the procedure have been examined in 20 patients with obstructive jaundice of uncertain origin and in one further patient with a post-cholecystectomy syndrome. The presence and the nature of extrahepatic obstructive lesions was correctly diagnosed in 10 of 11 patients shown to have this cause for jaundice. The failure to obtain cholangiograms in the remaining 10 patients was correctly correlated with the presence of intrahepatic obstructive disease due to hepatitis or primary biliary cirrhosis. The risks of percutaneous cholangiography seem over-rated, biliary peritonitis occurring in under 5% of patients submitted to the procedure.